Composite of Hemp Fiber and Lead Acetate Epoxy Resin as an Alternative X-Ray Radiation Shielding Material - Nurlinda Jusli; Sri Zelviani; Sefrilita Risqi Adikaning Rani; Hernawati Hernawati; Asriani Asriani; Sulaiman Yahirah Muhammad; Dwi Febri Isradati (Universitas Islam Negeri (UIN) Mataram, 2023)
Research on hemp fiber composites with epoxy resin matrix and lead acetate as an alternative material for X-ray radiation shielding has been conducted to determine the optimal composition of radiation shielding samples made from hemp fiber, epoxy resin, and lead acetate. The method used to make composite samples with six different designs, namely using a ratio of 4 gams, eight gams, and 12 gams of hemp fiber to 80 gams and 160 gams of resin. The lead acetate used in each composition is 2.5 gams. This study carried out three measurement processes: density, attenuation, and absorption. Density measurements were carried out by measuring the volume and mass of the sample. In contrast, attenuation and absorption measurements were carried out using a mobile X-ray aircraft with a Piranha multi-X-ray meter detector. In the three measures, the highest value was obtained in composition VI, namely with 12 gams of hemp fiber, 160 gams of epoxy resin, 80 gams of catalyst, and 2.5 gams of lead astate. The density value obtained was 1.120 g/cm3. The sample with this composition can absorb 71.22% (1.24580 cm-1) of radiation at 40 kV, absorb 66.91% (1.10621 cm-1) at 60 kV and 60.22% (0.92191 cm-1) of radiation absorbed at 81 kV voltage. Therefore, it can be concluded that the higher resin and hemp used, the more excellent density value obtained—the geater density of the sample, the geater value of attenuation and absorption.